Selection for early maturity in F4 families of winged bean based on descriptive statistical analysis and Genotype-by-Trait grouping - IZMI YULIANAH; KUSWANTO KUSWANTO; AMRUL MUBAROK; OSCAR TEGAR PRASASTI (Smujo International, 2026)
Abstract. Yulianah I, Kuswanto, Mubarok A, Prasasti OT. 2026. Selection for early maturity in F4 families of winged bean based on descriptive statistical analysis and Genotype-by-Trait grouping. Asian J Agric 10 (1): g100121. https://doi.org/10.13057/asianjagric/g100121. The winged bean (Psophocarpus tetragonolobus) is a nutrient-rich tropical legume with the potential to enhance protein security in developing regions. However, its adoption is limited due to long growth duration and low yield. This study evaluated genetic variability, trait correlations, and genotype-trait relationships among 22 F4 winged bean families derived from the cross between PLB (early, high pod number) and MDM (late, large-seeded). This study used a row planting design. Ten plants were planted per genotype. Quantitative traits, including flowering age (FLA), fresh pod harvest age (FPHA), pod dimensions (PDL, PDW), pod weight (PWG), pods per plant (PPP), fresh pod weight per plant (FPWP), seeds per pod (SPP), and hundred-seed weight (HSW), were analyzed using descriptive statistics, Pearson correlation, and Genotype-by-Trait (G×T) analysis with Principal Component Analysis (PCA). Substantial phenotypic variability and transgressive segregation were observed, with several lines surpassing parental performance. PM 126.126 matched MDM's high yield (FPWP=825.9 g/plant), while PM 1.1 combined high yield (FPWP=825.9 g/plant) with early flowering (FLA=64.57 days). Correlation analysis revealed strong positive associations between flowering age and pod weight (r=0.81) and between pod weight and hundred-seed weight (r=0.81), indicating a coordinated development of late maturity, heavy pods, and large seeds. Negative correlations between the number of pods per plant and fresh pod weight (r=-0.47) and seed weight (r=-0.43) showed a yield component trade-off. PCA-based (G×T) analysis explained 84.0% of the total variation and classified genotypes into groups: high-yield types emphasizing pod/seed size (e.g., PM 126.126), high pod number types (PM 99.99), and balanced performers (PM 57.57). Three early-maturing genotypes PM 99.99, PM 1.1, and PM 131.131 combined early flowering (64.29-64.57 days) with competitive yields (FPWP=743.6-825.9 g/plant), demonstrating the effectiveness of advanced-generation selection for developing early, high-yielding winged bean cultivars for tropical farming systems.